2004
DOI: 10.1179/037195504225005750
|View full text |Cite
|
Sign up to set email alerts
|

The heat treatment and particle size effects in the thermal decomposition of dolomite for separation of constituents

Abstract: The effect of particle size and heat treatment on partial decomposition of dolomite for the extraction of calcite has been investigated. Isothermal firing trials varying the soaking period were performed for dolomite at temperatures between 1013-1033 K according to schedules derived from thermogravimetric analysis (TGA). Samples of dolomite representing three size fractions were used. It is shown that, the optimum heat treatment for reducing the residual MgO in extracted CaCO 3 and maximising the yield of CaCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Dependiendo de las condiciones experimentales, la descomposición térmica puede proceder en una etapa endotérmica en aire (De Aza et al, 2002;Engler et al, 1989;Fang et al, 2011;Subagjo et al, 2017;Wiedemann y Bayer, 1987), nitrógeno (Bogahawatta et al, 2004;Wiedemann y Bayer, 1987), argón y helio (Smith et al, 1974), o en CO2 a una presión menor de 150 mm de Hg, de acuerdo a la ecuación (Otsuka, 1986;Santani et al, 2001) (Ecuación 3):…”
Section: Comportamiento Térmicounclassified
See 1 more Smart Citation
“…Dependiendo de las condiciones experimentales, la descomposición térmica puede proceder en una etapa endotérmica en aire (De Aza et al, 2002;Engler et al, 1989;Fang et al, 2011;Subagjo et al, 2017;Wiedemann y Bayer, 1987), nitrógeno (Bogahawatta et al, 2004;Wiedemann y Bayer, 1987), argón y helio (Smith et al, 1974), o en CO2 a una presión menor de 150 mm de Hg, de acuerdo a la ecuación (Otsuka, 1986;Santani et al, 2001) (Ecuación 3):…”
Section: Comportamiento Térmicounclassified
“…oxígeno; en CO2 se presenta una descomposición en tres etapas (Ptáček et al, 2021). En un proceso en dos etapas, a presión de CO2 mayor a 150 mm de Hg, la descomposición térmica procede como sigue (Ecuaciones 4 y 5) (Bogahawatta et al, 2004;Kristóf-Makó y Juhász, 1999;Santani et al, 2001):…”
Section: Comportamiento Térmicounclassified
“…The relative amounts of these phases depend on the specific temperature, heating time, and the ambient CO 2 pressure . It has been found that the yield of MgO can be maximized and that of CaO minimized by heating dolomite at 740 °C in a pure CO 2 atmosphere. , The smaller size of Mg 2+ compared to Ca 2+ results in a greater mobility of magnesium in the dolomite structure, and thus, the easier detachment and escape of carbon dioxide associated to magnesium oxide during calcination. So the formation of MgO is kinetically favored over that of CaO .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the chemical composition of the dolomite powder, consisting of more than 5% wt., CaO and MgO (Małolepszy et al 1994, Konik et al 2007, Kurdowski 2010, the material cannot be considered as potential replacement for clinker in cement production, even though the studies on calcination were promising because of the mineral phases formed. On the other hand, while the procedure of MgO extraction from dolomite is normally used (Beruto et al 2003, Bogahawatta et al 2004, the MgO extraction experiment from dolomite powder could be investigated. According to results obtained by Rashad and Baioumy (2005), MgO recovery was increased by decreasing the particle size.…”
Section: Leaching Testsmentioning
confidence: 99%